Histone methylation is critical in monocyte to macrophage differentiation. (2nd May 2017) - Bermick, Jennifer; Schaller, Matthew; Carson, William
Abstract : Monocyte derived macrophages contribute to many human diseases, and a prescribed set of transcription factors control the differentiation of monocytes into macrophages. In this issue of The FEBS Journal, Jin and colleagues demonstrate that histone methylation changes in monocytes alter chromatin structure and ultimately direct the expression of numerous transcription factors crucial in this differentiation process.